2013
DOI: 10.1109/titb.2012.2199128
|View full text |Cite
|
Sign up to set email alerts
|

On the Relevance of Glycolysis Process on Brain Gliomas

Abstract: The proposed analysis considers aspects of both statistical and biological validation of the glycolysis effect on brain gliomas, at both genomic and metabolic level. In particular, two independent datasets are analyzed in parallel, one engaging genomic (Microarray Expression) data and the other metabolomic (Magnetic Resonance Spectroscopy Imaging) data. The aim of this study is twofold. First to show that, apart from the already studied genes (markers), other genes such as those involved in the human cell glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The glycolysis pathway is related to VaD, and genes involved in this pathway, such as GPI and GAPD, are significantly downregulated in the AD hippocampus [31,35]. In addition, PFKM, PGM1, ALDOA, and ALDOC are also downregulated in the entorhinal cortex of AD patients [32,36,37]. Our study showed that downregulated proteins were significantly enriched in the subpathways of the ‘glycolysis/gluconeogenesis' pathway.…”
Section: Discussionmentioning
confidence: 87%
“…The glycolysis pathway is related to VaD, and genes involved in this pathway, such as GPI and GAPD, are significantly downregulated in the AD hippocampus [31,35]. In addition, PFKM, PGM1, ALDOA, and ALDOC are also downregulated in the entorhinal cortex of AD patients [32,36,37]. Our study showed that downregulated proteins were significantly enriched in the subpathways of the ‘glycolysis/gluconeogenesis' pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Heightened expression of LDHB may contribute to tumor acidity, and growth (24) known to occur in parallel to activated RTK-PI3K-AKT-mTOR signaling (25) and is observed in various types of cancer including bladder (26) merkel cell carcinoma (27) lung cancer (28) glioma (29) or maxillary sinus squamous cell carcinoma, most reporting its association with poor survival rates (30). …”
Section: Discussionmentioning
confidence: 99%
“…Related study has shown that the combination of glycolytic genes, including PFKM , ALDOA , ALDOC , and PGM1 , participates in the glycolytic process. 29 6-Phosphofructokinase, muscle type is a regulatory protein coded by PFKM . It can transform fructose-6-phosphate into fructose-1,6-bisphosphate (F-1, 6-BP) in glycolysis, which is a key procedure in glycolysis.…”
Section: Discussionmentioning
confidence: 99%